Ice water test in multiple sclerosis: A pilot trial. (13th August 2018) - Hüsch, Tanja; Reitz, André; Ulm, Kurt; Haferkamp, Axel
Abstract : Objectives: To investigate the significance of the ice water test in patients with multiple sclerosis and to evaluate a novel ice water test nomogram in a large patient cohort. Methods: A total of 201 ice water tests of patients with multiple sclerosis were retrospectively evaluated. Incontinence episodes in 24 h and sex were correlated with the ice water test. Furthermore, an ice water test nomogram was developed in order to categorize the detrusor overactivity in severity degrees. Descriptive statistics were carried out for population characteristics. Correlations of categorical variables were calculated by the χ 2 ‐test. The independent t ‐test was carried out for correlations of continuous variables. Furthermore, the data were evaluated in the novel ice water test nomogram. Results: The patient population consisted of 141 (70.1%) women and 60 (39.9%) men. A clinically positive ice water test (maximum detrusor pressure >15 cmH2 O) was identified in 75 patients (37.3%). Significantly more men presented a clinically positive ice water test ( P  = 0.006). In 16.5%, the ice water test unmasked an involuntary detrusor contraction, although routine cystometry did not show any detrusor overactivity. The ice water test nomogram could be successfully applied. The incontinence episodes and maximum detrusor pressure correlated positively with a higher categorization in the nomogram. Therapeutic interventions and follow‐up controls could be successfully illustrated by the nomogram. Conclusions: The ice water test is a simple tool for unmasking non‐identified detrusor overactivity in neurogenic bladder dysfunction. A severity categorization of the detrusor overactivity can be facilitated by the use of the ice water test nomogram. After further validation, the ice water test could be ultimately used in future as objective assessment for bladder dysfunction.